LEGAL REGULATION OF AIR POLLUTION IN URBAN ENVIRONMENTS AT THE LEVEL OF THE EUROPEAN UNION AND CONSEQUENCES OF POLLUTION - Bugarski, Tatjana; Tubić, Bojan; Pisarić, Milana (Zbornik radova Pravnog fakulteta u Novom Sadu, 2020)
Air pollution in urban areas is currently one of the most pronounced risks to the environment and human health. Regulations at the level of the European Union require Member States to monitor and control the concentration of certain pollutants in the air, especially in urban areas. However, despite the fact that there is a legal framework for controlling the concentration of air pollutants, the data show that a number of Member States fail to meet air quality standards, and thus to protect the health of the population. This paper presents individual air quality standards in urban areas at the level of the European Union and analyzes the application of these standards through several examples. In addition, the multiple importance of the control system for the concentration of certain air pollutants in urban areas was pointed out, in terms of the impact of polluted air on human behavior and the growth of crime rates.